Vertical distribution of bacterioplankton in Lake Averno in relation to water chemistry. Issue 1 (31st December 2012) - Paganin, Patrizia; Chiarini, Luigi; Bevivino, Annamaria; Dalmastri, Claudia; Farcomeni, Alessio; Izzo, Giulio; Signorini, Antonella; Varrone, Cristiano; Tabacchioni, Silvia
Abstract: The effects of environmental factors on bacterioplankton distribution along the water column of Lake Averno (Naples, Italy) have been investigated by means of denaturing gradient gel electrophoresis (DGGE) of polymerase chain reaction (PCR)‐amplified 16S rRNA gene fragments, and multivariate analysis applied to molecular data and physico‐chemical parameters. Bacterial richness, estimated from DGGE profiles, remains constant throughout the water column, whereas archaeal richness increases with depth. Moreover, archaeal richness was significantly correlated to most of the measured abiotic variables, whereas bacterial richness did not. Analysis of sequences from DGGE bands revealed that the dominant bacterial populations belong to Alphaproteobacteria, Betaproteobacteria, Deltaproteobacteria, Bacteroidetes and Firmicutes, whereas sequences of the archaeal DGGE bands are affiliated to Methanomicrobiales and Methanosarcinales orders. Moreover, bacterial sequences affiliated to Proteobacteria and Bacteroidetes do not group closely to typical freshwater lineages/clades/tribes within these phyla. Bacterioplankton distribution along the water column was apparently correlated with the vertical gradient of physico‐chemical parameters as a statistically significant relationship between most of them with grouping of specific taxonomic units was observed.